Teens and Sexual Harassment: Making a Difference: FCS2249/FY850, 10/2006 - Fogarty, Kate (EDIS, 2006)
FCS-2249, a 6-page fact sheet by Kate Fogarty, is one of a series of discussions on understanding teen sexuality, intended for adults who work with teens. It defines sexual harassment and how it can manifest at school, in the workplace, and in cyberspace; discusses how sexual harassment affects teens; and provides some suggestions to offer teens, parents, and educators on how to handle it. Includes references and additional resources for teens and parents. Published by the UF Department of Family Youth and Community Sciences, October 2006. FCS2249/FY850: Teens and Sexual Harassment: Making a Difference (ufl.edu)